Analisis Pengakuan Pendapatan Kontrak Konstruksi Berdasarkan PSAK 34 Dengan Persentase Penyelesaian Pada CV. Indra Surya - Widia Rahma Warnika; Martinus Budiantara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
In the method of recognizing revenue in construction companies, there are two different methods, namely the completed contract method and the percentage of completion method. The completed contract method is a method that takes into account the profit and loss at the end of the contract, while the percentage of completion method is a method that recognizes profit and loss based on the percentage of work completed in each period. The percentage of completion method has two approaches, namely physical and cost-to-cost.The purpose of this research is to find out whether the income recognition method with the percentage of completion on CV. Indra Surya is in accordance with PSAK 34. The analytical method used in this study is descriptive qualitative with comparative descriptive, in which the researcher analyzes the suitability of income recognition in CV. Indra Surya with theory from PSAK 34. Data collected through observation or surveys, field studies, and documentation. The results showed that CV. Indra Surya applies the recognition of revenue recognition using the percentage of completion method based on PSAK 34 .